Evaluating is not the Key!

x = 0 15 ( x ( 25 x ) ( 15 15 x ) ( 40 15 ) ) \large \sum_{x=0}^{15} \left( x \cdot \dfrac{ {25 \choose x} \cdot {15 \choose 15-x} }{ {40 \choose 15} } \right)

If the summation above simplifies to a b \dfrac ab , where a a and b b are coprime positive integers, find a + b a+b .


The answer is 83.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Feb 2, 2017

Suppose that a class of 40 40 students contains 25 25 boys and 15 15 girls. A team of 15 15 players is chosen at random, and N N is the number of boys it contains. Then P [ N = x ] = ( 25 x ) ( 15 15 x ) ( 40 15 ) 0 x 15 \mathbb{P}[N = x] \; = \; \frac{\binom{25}{x} \binom{15}{15-x}}{\binom{40}{15}} \hspace{2cm} 0 \le x \le 15 so we are intetested in calculating E [ N ] = x = 0 15 x ( 25 x ) ( 15 15 x ) ( 40 15 ) \mathbb{E}[N] \; = \; \sum_{x=0}^{15} x \frac{\binom{25}{x} \binom{15}{15-x}}{\binom{40}{15}} Evaluating this expectation can be done easily using indicator random variables. The team lines up for a photograph. Then N = N 1 + N 2 + N 3 + + N 15 N = N_1 + N_2 + N_3 + \cdots + N_{15} where N j N_j is the random variable that is equal to 1 1 if the j j th player from the left is a boy, and 0 0 if that player is a girl. Then E [ N ] = j = 1 15 E [ N j ] \mathbb{E}[N] \; = \; \sum_{j=1}^{15} \mathbb{E}[N_j] But E [ N j ] \mathbb{E}[N_j] is just the probability that (independent from all the other players chosen) the j j th player is a boy, and this is 25 40 \tfrac{25}{40} . Thus E [ N ] = 15 × 25 40 = 75 8 \mathbb{E}[N] \; = \; 15 \times \tfrac{25}{40} \; = \; \tfrac{75}{8} making the answer 75 + 8 = 83 75+8=\boxed{83} .

Christian Daang
Feb 2, 2017

Relevant wiki: Vandermonde's Identity

We know that: ( n k ) = n ! k ! ( n k ) ! this can be transformed to: ( n k ) = n k ( n 1 ) ! ( k 1 ) ! ( n 1 ( k 1 ) ) ! = n k ( n 1 k 1 ) Now we can start with the definition of the expected value: E [ X ] = x = 0 n x ( K x ) ( M K n x ) ( M n ) Since for x=0, we add a 0 in this formula we can say that: E [ X ] = x = 1 n x ( K x ) ( M K n x ) ( M n ) \large {\text{We know that:} \ \binom{n}{k} = \cfrac{n!}{k!(n-k)!} \cdot \ \text{this can be transformed to:} \\ \binom{n}{k}=\cfrac{n}{k}\frac{(n-1)!}{(k-1)!(n-1-(k-1))!}=\cfrac{n}{k} \binom{n-1}{k-1} \cdot \\ \text{Now we can start with the definition of the expected value: } \ E[X]=\sum_{x=0}^{n} \cfrac{x{K\choose x}{M-K\choose n-x}}{M\choose n} \cdot \\ \text{Since for x=0, we add a 0 in this formula we can say that: } \ E[X]=\sum_{x=1}^{n}\cfrac{x{K\choose x}{M-K\choose n-x}}{M\choose n} \cdot}

Applying equation (1) we get: E [ X ] = n K M x = 1 n ( K 1 x 1 ) ( M 1 ( K 1 ) n 1 ( x 1 ) ) ( M 1 n 1 ) setting l = x - 1: E [ X ] = n K M l = 0 n 1 ( K 1 l ) ( M 1 ( K 1 ) n 1 l ) ( M 1 n 1 ) The sum of this equation: l = 0 n 1 ( K 1 l ) ( M 1 ( K 1 ) n 1 l ) ( M 1 n 1 ) is 1 as it is the over all sum of the probabilities of a hypergeometric distribution (Vandermonde’s Identity) \large { \text{Applying equation (1) we get: } \\ E[X]=\cfrac{nK}{M} \sum_{x=1}^{n} \cfrac{\binom{K-1}{x-1} \binom{M-1-(K-1)}{n-1-(x-1)}}{\binom{M-1}{n-1}} \cdot \\ \text{setting l = x - 1: } \implies E[X]=\cfrac{nK}{M} \sum_{l=0}^{n-1} \cfrac{\binom{K-1}{l} \binom{M-1-(K-1)}{n-1 -l}}{\binom{M-1}{n-1}} \cdot \\ \text{The sum of this equation:} \ \sum_{l=0}^{n-1} \cfrac{\binom{K-1}{l} \binom{M-1-(K-1)}{n-1 -l}}{\binom{M-1}{n-1}} \ \text{is 1 as it is the over all sum of the probabilities of a hypergeometric distribution (Vandermonde's Identity)} \cdot}

Interpretation: Each term in the above sum can be interpreted as probability, that is the probability distribution of number of the number of blue balls in n 1 n-1 draws without replacement from a bag containing K 1 K-1 blue and M 1 ( K 1 ) M-1-(K-1) green balls.

Therefore we have: E [ X ] = n K M hence, the problem x = 0 15 ( x × ( 25 x ) × ( 15 15 x ) ( 40 15 ) ) is just the same as: E [ X ] = x = 0 n x ( K x ) ( M K n x ) ( M n ) = n K M where n = 15, K = 25, M = 40. x = 0 15 ( x × ( 25 x ) × ( 15 15 x ) ( 40 15 ) ) = n K M = 15 × 25 40 = 75 8 a + b = 75 + 8 = 83. \large {\text{Therefore we have:} \ E[X]=\cfrac{nK}{M} \cdot \\ \text{hence, the problem} \ \sum_{x = 0}^{15} \left( x \times \cfrac{\binom {25}{x} \times \binom {15}{15-x}}{\binom {40}{15}}\right ) \ \text{is just the same as:} \ E[X]=\sum_{{x=0}}^{n}\cfrac{x{K\choose x}{M-K\choose n-x}}{{M\choose n}} = \cfrac{nK}{M} \ \text{where n = 15, K = 25, M = 40.} \\ \implies \sum_{x = 0}^{15} \left( x \times \cfrac{\binom {25}{x} \times \binom {15}{15-x}}{\binom {40}{15}}\right ) = \cfrac{nK}{M} = \cfrac{15\times 25}{40} = \cfrac{75}{8} \\ \implies \boxed{a + b = 75 + 8 = 83.}}

FYI avoid having chunks of text placed in Latex. Just type normally, and use the Latex brackets for equations.

Calvin Lin Staff - 4 years, 4 months ago

Log in to reply

ok sir, thanks again. :)

Christian Daang - 4 years, 4 months ago
Kushal Bose
Feb 10, 2017

Its simply the co-efficient of x 14 x^{14} in 25 ( 1 + x ) 24 ( x + 1 ) 15 25 (1+x)^{24} (x+1)^{15}

How did you know this? Can you elaborate on it?

Pi Han Goh - 4 years, 4 months ago

please elaborate it will help others....

space sizzlers - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...